Collectivism and individualism in Latino recovery homes. Issue 3 (3rd July 2018) - Jason, Leonard A.; Luna, Roberto D.; Alvarez, Josefina; Stevens, Ed
ABSTRACT: Research indicates that Latinos underutilize substance abuse interventions; cultural variables may contribute to difficulties accessing and completing treatment for this group. As a result, there is a need to understand the role of cultural constructs in treatment outcomes. The purpose of this study was to investigate how levels of collectivism (COL) and individualism (IND) relate to length of stay and relapse outcomes in self-run recovery homes. We compared Latinos in several culturally modified recovery Oxford Houses to Latinos in traditional recovery Oxford Houses. By examining COL and IND in the OH model, we explored whether aspects of COL and IND led to longer lengths of stay and better substance use outcomes. We hypothesized that higher levels of COL would predict longer stays in an Oxford House and less relapse. COL did not have a main effect on length of stay. However, COL had a significant interaction effect with house type such that COL was positively correlated with length of stay in traditional houses and negatively correlated with length of stay in the culturally modified condition; that is, those with higher collectivism tended to stay longer in traditional houses. When we investigated COL, length of stay, and substance use, COL was negatively correlated with relapse in the culturally modified houses and positively correlated with relapse in the traditional houses. In other words, those with higher COL spent less time and had less relapse in the culturally modified compared to the traditional Oxford Houses. The implications of these findings are discussed.